Suicidal ideation, burnout, and their correlation among health care workers at the end of the fourth wave of the COVID-19 pandemic in Alborz Province, Iran - Badrfam, Rahim; Zandifar, Atefeh; Mohammadian Khonsari, Nami; Qorbani, Mostafa (Frontiers in Psychiatry, 2023)
Background: During the COVID-19 pandemic, Health Care Workers (HCWs) were more vulnerable than ever to Burnout and Suicidal thoughts due to stressful work conditions. This study, investigated the level of Burnout and Suicidal thoughts among HCWs during the fourth wave of the pandemic in Alborz Province in Iran and compared it with the conditions at the beginning of the pandemic.A cross-sectional study was carried out with a sample of HCWs dealing with COVID-19 patients using the available sampling method. The results of this online survey, which was conducted from June 7 to July 5, 2021 (at the end of the Fourth Wave of the COVID-19 Pandemic in Iran), have been compared with the conditions of the First Wave of the Pandemic (from February 24 to April 27, 2020). The participants were evaluated by the Beck Scale for Suicidal Ideations (BSSI) and Maslach Burnout Inventory (MBI) .Results: A total of 305 HCWs from 3 referral hospitals for COVID-19, including 155 men and 150 women, participated in the study. The mean age of the participants was 36.34 ± 7.37. The means of Suicide Index (SI), Emotional Exhaustion (EE), Depersonalization (DP), and Personal Accomplishment (PA) scores were 0.76 ± 1. 74, 19.94 ± 4.69, 4.92 ± 1.51, and 31.30 ± 5.88, respectively. SI and PA were significantly higher in workers other than nurses and physicians and EE was higher among workers with night shifts (P value<0.05 in all indices). Age had a significant and negative correlation with EE (P value<0.01) and DP (P value<0.05) and a significant and positive correlation with PA (P value<0.01).This study showed a high level of SI and Burnout indices among HCWs in the fourth wave of the pandemic in Iran. Paying attention to the factors affecting the development of social capital and creating health policy changes may be effective in reducing Burnout indices and high Suicide index among HCWs.